Course management systems for learning beyond accidental pedagogy - McGee, Patricia, 1953-; Carmean, Colleen, 1955-; Jafari, Ali. (Hershey PA : Information Science Pub., 2005)
"This book provides a comprehensive overview of standards, practices and possibilities of course management systems in higher education"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Universities and colleges -- Curricula; Education, Higher -- Computer-assisted instruction; Student-centered learning